2015
DOI: 10.1021/acs.organomet.5b00615
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection, Dimerization, and Chemical Trapping of Dimethyl- and Diphenylstannylene from Photolysis of Stannacyclopent-3-enes in Solution

Abstract: Dimethyl- and diphenylstannylene (SnMe2 and SnPh2, respectively) have been successfully detected and characterized in solution. The stannylenes were generated by photolysis of 1,1,3-trimethyl-4-phenyl- (2) and 3,4-dimethyl-1,1-diphenylstannacyclopent-3-ene (3), respectively, which have been shown to extrude the species cleanly and in high (0.6 < Φ < 0.8) quantum yields through trapping studies using dichlorodimethylstannane (Me2SnCl2) as the stannylene substrate. Laser flash photolysis of 2 and 3 in deoxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 124 publications
1
7
0
Order By: Relevance
“…In addition, the relatively large C(6)–Sn(2)–Sn(1)–C(3) angle indicates that a (C(3)) methyl or ethyl substituent is aligned with the empty p-orbital on the Sn(2) atom which lies perpendicular to the coordination plane at Sn(2), suggesting incipient methyl or ethyl bridging. This is consistent with the calculated transition state for the conversion of the related distannene­(SnPh 2 ) 2 to its asymmetric isomer PhSnSnPh 3 …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the relatively large C(6)–Sn(2)–Sn(1)–C(3) angle indicates that a (C(3)) methyl or ethyl substituent is aligned with the empty p-orbital on the Sn(2) atom which lies perpendicular to the coordination plane at Sn(2), suggesting incipient methyl or ethyl bridging. This is consistent with the calculated transition state for the conversion of the related distannene­(SnPh 2 ) 2 to its asymmetric isomer PhSnSnPh 3 …”
Section: Resultssupporting
confidence: 90%
“…This is consistent with the calculated transition state for the conversion of the related distannene(SnPh 2 ) 2 to its asymmetric isomer PhSnSnPh 3 . 43 The structural data for Ar 4, left) reveal it to have an asymmetric monohydrido stannylstannylene structure. The Sn(1) atom has a distorted tetrahedral coordination and is bound to its partner tin atom Sn(2), a t-butylethyl group, a terphenyl ligand, and a hydride with a Sn−H distance of 1.575(7) Å.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The tetrylenes of the heavier group 14 elements (:ER 2 , E = Si, Ge, Sn, or Pb; R = bulky substituent) have an extensive chemistry that has been investigated for over four decades. They are characterized by a singlet ground state in which a nonbonded electron pair occupies one of the two valence orbitals and which may function as an electron pair donor. The existence of an adjacent unoccupied p-orbital allows the tetrylenes to behave as donor–acceptor molecules in a synergistic manner, and this has enabled their facile reactions with small molecules such as H 2 , NH 3 , CO, and C 2 H 4 . , The insertion chemistry of group 14 metalylenes has also been especially well documented through reactions with the aforementioned small molecules as well as with organohalides, transition metal halides, H 2 O, MeOH, , N 2 H 4 , the group 13 alkyls AlMe 3 and GaR 3 (R = Me, Et), and white phosphorus P 4 . These insertions have proven useful for the synthesis of uncommon bond types in molecular species, such as Ge–Al, Sn–Al, and Sn–Ga bonds.…”
Section: Introductionmentioning
confidence: 99%
“…A logical extension of this chemistry is the investigation of the reactions of E­(Ar Me 6 ) 2 with hydroxyl compounds and of water and methanol in particular. Although the insertion of transient tetrylenes such as EH 2 , EMe 2 , or EPh 2 (E = Si, Ge, or Sn) into O–H bonds has been studied both experimentally and theoretically, there are only a few examples of similar reactions involving stable acyclic tetrylenes that yield structurally characterized products. Most notably, Lappert et al have reported the crystallographic characterization of {(Me 3 Si) 2 CH} 2 Ge­(H)­OEt from the reaction of Ge­{CH­(SiMe 3 ) 2 } 2 with ethanol, while Pörschke et al obtained {(Me 3 Si) 2 CH} 2 Sn­(H)­OH by reacting Sn­{CH­(SiMe 3 ) 2 } 2 with excess water .…”
Section: Introductionmentioning
confidence: 99%